Pendampingan dan Pemberdayaan Perempuan Melalui Inovasi Ikan Bandeng Untuk Meningkatkan Kemandirian Ekonomi Masyarakat - Majid, Makhrajani; Anggraini, Ayu Andira; M.S, Sukmah; Tasrik, Andi Muhammad Farid Faqih; Alghifari, Muh; Marshanda, Andriani; nas, Herawati; Natsir, Achmad; Nasir, Akram; Adzans, Nur (Abdimas Mandalika, 2025)
Abstract:  This community service program aimed to enhance the economic independence of coastal women through milkfish processing innovation to create value-added products. The program was conducted in Lampa Village, Duampanua District, Pinrang Regency, involving 20 women from local small business groups. The methods included socialization, technical training in milkfish floss production, workshops on branding and packaging design, digital marketing training using WhatsApp Business, and ongoing business mentoring. Evaluation was carried out through observation, interviews, and pre–post test questionnaires to measure skill improvement and economic impact. The results showed a significant increase in participants’ technical and managerial skills. Milkfish processing ability improved from 35% to 85%,  packaging skills increased from 25% to 75%, and digital marketing knowledge rose from 20% to 70%. Moreover, participants’ household income grew from 15% to 65%, indicating positive economic impact despite being in the early stage. The produced milkfish floss became more hygienic, durable, and attractively packaged, making it marketable. The program also encouraged the formation of a women’s business group actively developing local village-based products.Abstrak: Kegiatan pengabdian kepada masyarakat inbertujuan untuk meningkatkan kemandirian ekonomi perempuan pesisir melalui inovasipengolahan ikan bandeng menjadi produk bernilai tambah. Program dilaksanakan di Desa Lampa, Kecamatan Duampanua, Kabupaten Pinrang dengan melibatkan 20 perempuan anggota kelompok usaha lokal. Metode yang digunakan meliputi penyuluhan, pelatihan teknis pembuatan abon ikan bandeng, workshop branding dan desain kemasan, pelatihan pemasaran digital menggunakan WhatsApp Business, serta pendampingan usaha. Evaluasi dilakukan melalui observasi, wawancara, dan angket pre–post test untuk mengukur peningkatan keterampilan dan dampak ekonomi. Hasil kegiatan menunjukkan peningkatan signifikan pada keterampilan teknis dan pemahaman manajerial peserta. Kemampuan pengolahan ikan bandeng meningkat dari 35% menjadi 85%, keterampilan pengemasan naik dari 25% menjadi 75%, dan pengetahuan pemasaran digital meningkat dari 20% menjadi 70%. Selain itu, pendapatan keluarga peserta naik dari 15% menjadi 65%, menandakan adanya dampak ekonomi positif meskipun masih tahap awal. Produk abon bandeng yang dihasilkan kini lebih higienis, tahan lama, dan dikemas menarik sehingga layak dipasarkan. Program ini juga mendorong terbentuknya kelompok usaha perempuan yang aktif mengembangkan produk lokal unggulan desa.